A Systematic Study of Magnetic Field in Relativistic Heavy-Ion Collisions in the RHIC and LHC Energy Regions - Yang Zhong; Chun-Bin Yang; Xu Cai; Sheng-Qin Feng (Advances in High Energy Physics)
The features of magnetic field in relativistic heavy-ion collisions are systematically studied by using a modified magnetic field model in this paper. The features of magnetic field distributions in the central point are studied in the RHIC and LHC energy regions. We also predict the feature of magnetic fields at LHC sNN=900, 2760, and 7000 GeV based on the detailed study at RHIC sNN=62.4, 130, and 200 GeV. The dependencies of the features of magnetic fields on the collision energies, centralities, and collision time are systematically investigated, respectively.